Serum cytokine and chemokine profiles in patients with myasthenia gravis. (9th April 2014) - Uzawa, A; Kawaguchi, N; Himuro, K; Kanai, T; Kuwabara, S
Summary: Myasthenia gravis (MG) is an autoimmune-mediated inflammatory disease of the neuromuscular junction. Previous studies of animal MG models have suggested important roles of cytokines in MG pathogenesis, but adequate studies on cytokines in human MG are lacking. Using a multiplex suspension array system, we measured the serum levels of 27 cytokines/chemokines in 47 anti-acetylcholine receptor antibody-positive patients with MG and 20 normal controls (NC) to investigate the contribution of cytokines/chemokines toward MG pathogenesis. Correlations between clinical parameters and cytokine/chemokine levels in patients with MG were also examined. The serum levels of interleukin (IL)-15 (mean ± standard deviation: 6·85 ± 6·97 pg/ml) and vascular endothelial growth factor (VEGF) (96·21 ± 71·60 pg/ml) significantly increased, whereas IL-4 levels (3·57 ± 0·86 pg/ml) decreased in patients with MG compared with NC (IL-15: 4·42 ± 1·55 pg/ml; VEGF: 63·51 ± 32·95 pg/ml; IL-4: 4·15 ± 0·81 pg/ml, P < 0·05). In addition, eight cytokines (IL-4, IL-8, IL-15, eotaxin, macrophage inflammatory protein-1α, macrophage inflammatory protein-1β, VEGF and IL-1b) were significantly changed among MG patients with thymoma, MG patients without thymoma and NC ( P < 0·05). Some cytokines, such as IL-4, IL-15, and VEGF, may play roles in the pathogenesis of MG.